2018
DOI: 10.2147/jpr.s158877
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between diabetes and neck pain and lower back pain? Results of a population-based study

Abstract: BackgroundThe objective of the study was to study the association between low back pain (LBP), neck pain (NP), and diabetes while controlling for many sociodemographic characteristics, comorbidities, and lifestyle variables. The study also aimed to identify which of these variables is independently associated with LBP and NP among diabetes sufferers.MethodsA case–control study using data taken from the European Health Interview Surveys for Spain was conducted in 2009/2010 (n=22,188) and 2014 (n=22,842). We sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
7
25
0
1
Order By: Relevance
“…Diabetes is increasing in prevalence worldwide, with possible serious implications 2. An association between diabetes and LBP has been indicated in some population studies 3 4. Other studies have suggested a relationship between increased blood glucose levels and LBP 5 6.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is increasing in prevalence worldwide, with possible serious implications 2. An association between diabetes and LBP has been indicated in some population studies 3 4. Other studies have suggested a relationship between increased blood glucose levels and LBP 5 6.…”
Section: Introductionmentioning
confidence: 99%
“…Bone turnover markers (BTMs), which is an indicator for the rate of bone formation and resorption, has been shown to deteriorate in patients with T2DM as well 18. These signs and symptoms, combined with high prevalence of vertebral bone pain in the T2DM population, suggest that managing T2DM-induced bone disease is crucial to improving the patients’ quality of life and clinical outcomes 19…”
Section: Introductionmentioning
confidence: 99%
“…Neck pain is well known as one of the most common pain problems, and the reported prevalence ranges from 22-30 % [1][2][3]. It can result in significantly reduced quality of daily life and extensive use of healthcare resources [4][5][6].…”
Section: Introductionmentioning
confidence: 99%